KELAINAN BANGUN ANATOMIS KUKU KUDA KOLEKSI LABORATORIUM ANATOMI FKH IPB - A Dewangga, Kemaz; Sigit, Koeswinarning; -, Nurhidayat (Jurnal Veteriner, 2009)
The objective of this study is to observe the anatomical structure of horse hooves collected from the Laboratory of Anatomy FKH IPB. Twenty five hoof specimens, consisting of ten fore hooves and fifteen hind hooves were used as research materials. The external morphology such as color, angle, structure and condition of the hoof wall were described. The observation on external morphology showed that the hooves have two basic colors, black and white. Generally, all of the hoof specimens showed abnormalities in such aspect as angle, structure and condition of the wall. The structures of fore hoof and hind hoof from this study are classified into 8 categories, they are: flat foot, flared foot, knol hoef, fever rings, sand crack, club foot, contracted foot and bull nosed foot.
Keywords: anatomical structure, hoof